Classified Conversations: Psychiatry and Tactical Technical Communication in Online Spaces. Issue 1 (2nd January 2017) - Holladay, Drew
ABSTRACT: This article examines the practices of writers in online discussion board conversations as they interpret technical documents related to a psychiatric diagnosis. Drawing from interviews with 15 participants, the author argues that writers in this context interpret and manipulate medical knowledge in unique ways that benefit the community. The author concludes that studies in technical communication should take into account all groups affected by specialized knowledge, including those with little expertise or social power.